OLIY TA’LIM TEXNIKA YO‘NALISHLARIDA TAHSIL OLAYOTGAN TALABALARNING O‘ZBEK TILIDAGI MULOQOT MADANIYATINI RIVOJLANTIRISH - Ya.Shermatova, D. (SCIENCE and SOCIETY, 2023)
The article highlights the personal relationship that the main primary goal of the practical training classes of the native language, that is, the Uzbek language, is the proportional development of speech and thinking. In the education of students studying in the field of technology, it is suggested to use various effective methods and methods to develop the competence of professional communication in the Uzbek language, to develop the specific aspects of national communication and speech culture in them.